Rural youth transitions and structural change in sub-Saharan Africa: the rural path revisited - (:unkn) unknown (My University, 2020)
Demo-economic transitions in sub-Saharan Africa have led to an unprecedented increase in population, calling into question the capacity of current economic structures to ensure people’s livelihoods, as well as the reproduction of these livelihoods that allows societies to endure over time. In a globalized world facing climate change, this situation brings the debates about structural change patterns able to support demo-economic transitions in sub-Saharan Africa back to the forefront. Among these patterns, this PhD chooses to explore the rural and agricultural pattern. In order to inform this option pattern, the PhD has a specific approach that considers structural change as the evolution of socioeconomic reproduction patterns of rural African households.The originality of the approach taken by this PhD when analyzing this research subject lies in its combination of an institutional approach with a comparative and historical methodology, that examines socioeconomic transition among rural youth over a number of generations, thus enabling a long-term view. These transitions were built from the collection of original biographical data from 525 households in four rural areas in Senegal and Zambia.After the elaboration of a theoretical model in institutional economics, the PhD produces a typology of rural youth socioeconomic transitions from which generational changes in the modalities of youth transitions are identified. Linking these changes to the institutional framework of each generation of individuals leads to the identification of key institutions that determine socioeconomic reproduction patterns of rural households according to different contexts in rural Africa. Next, the PhD identifies the dependency relationship between the family farming model and the way generations of rural youth enter farming as a means of becoming economically active. The PhD states that the family farming model, historical pattern of socioeconomic reproduction of rural h
Keywords: African Research